PENGARUH KUALITAS PRODUK DAN PEPSEPSI HARGA TERHADAP SIKAP KONSUMEN DAN DAMPAKNYA TERHADAP NIAT BELI KONSUMEN SEPATU CONVERSE - Yanuar Rizki, 12.05.51.0098 (Students' Journal of Economic and Management, 2017)
This study attempts to analyze influence product quality and perception of consumer prices attitude and its impact on intention buy shoes converse consumers.The population research is consumers who buy shoes conversedi city semarang.sampel in this research as many as 100 people.Using techniques the sample purposive sampling.But sample criteria the research is customers who bought over and always shoes converse products.A the analysis used is the validity, reliability and linear regression berganda.hasil analysis it can be concluded that: product quality it has some positive effects in allah price konsumen.persepsi it has some positive effects in allah consumers.An influential positive on consumers buy intentions. Keywords: product quality, price perception, consumer attitudes and buying intentions